SOCIAL ADAPTATION OF CHILDREN - Turdieva Izzatoy Sadikovna (Journals Park Publishing, 2022)
Social-pedagogical interaction is an individual approach that allows to consider the social-pedagogical process to solve the child's social-pedagogical problems. This article discusses about the whole social adaptation of children.
Keywords: social adaptation, interaction, pedagogy, attitude, approach